A desterritorialização das escolas no campo do município de Dona Francisca/RS - Groff, Altair (2016)
This work aims to identify and think over the process of deterritorialization of the Countryside Schools of the city Dona Francisca/RS. Weaving a broad approach of the global context for the research action’s place in the city under this study, directed to education in order to better elucidate the cessation of these schools. The general purpose of this work is to understand the historical, environmental, social, economic and cultural processes that led to the deterritorialization of the Schools in the Countryside of the city Dona Francisca/RS. The specific objectives are: to identify the implementation of rural schools in the city; to verify the issues related to public policies in countryside education; and to argue about the possibilities and the limitations of permanence of the Tiradentes School in the countryside of the city Dona Francisca/RS. This research is arranged as a case study, using a qualitative approach, with observations in the communities, fieldwork, interviews, mapping and images capture. In this context, there is still a territorialized school, while the others have followed the reverse process, which means, the deterritorialization. Closed schools in the countryside denote the rural exodus, the disarticulation of the community, and disconnected public policies to the needs of working and needy population.